Revisit the rate of tidal disruption events: the role of the partial tidal disruption event - Zhong, Shiyan; Li, Shuo; Berczik, Peter; Spurzem, Rainer (The astrophysical journal, 2022)
Tidal disruption of stars in dense nuclear star clusters containing supermassive central black holes (SMBH) is modeled by high-accuracy direct N-body simulation. Stars getting too close to the SMBH are tidally disrupted, and a tidal disruption event (TDE) happens. The TDEs probe the properties of SMBHs, their accretion disks, and the surrounding nuclear stellar cluster. In this paper, we compare the rates of full tidal disruption events (FTDEs) with partial tidal disruption events (PTDEs). Since a PTDE does not destroy the star, a leftover object emerges; we use the term “leftover star” for it. Two novel effects occur in the simulation: (1) variation of the leftover star’s mass and radius and (2) variation of the leftover star’s orbital energy. After switching on these two effects in our simulation, the number of FTDEs is reduced by roughly 28%, and the reduction is mostly due to the ejection of the leftover stars from PTDEs originally coming from a relatively large distance. The number of PTDEs is about 75% higher than the simple estimation given by Stone et al., and the enhancement is mainly due to the multiple PTDEs produced by the leftover stars residing in the diffusive regime. We compute the peak mass fallback rate for the PTDEs and FTDEs recorded in the simulation and find that 58% of the PTDEs have a peak mass fallback rate exceeding the Eddington limit, and the number of super-Eddington PTDEs is 2.3 times the number of super-Eddington FTDEs.